Analysis of models: an alternative methodology of teaching characterized by a group of teachers of basic education (Research, Society and Development, 2018)
The main objective of this article is to identify how a group of Basic Mathematics teachers from the city of Uberlandia - MG characterizes the term “Analysis of Models”, based on the assumption that it is a methodological alternative of teaching, and that its relation with the Mathematical Modeling in the educational context. By means of a questionnaire on the topic, applied to the 17 participants, the reports that were analyzed were collected using the Discursive Textual Analysis as a research method. The analysis points out that the research participants characterize “Model Analysis” in three different ways, according to the emerging categories of their reports: as a teaching approach that uses mathematical models ready to understand real phenomena through mathematical language; solve problem situations arising from real phenomena; and as a step within a process of Mathematical Modeling. These categories show that there is a close relationship between "Model Analysis" and Mathematical Modeling, either as the use of models derived from a modeling process or as an integral part of this process.